Enteral feed based gradual improvement of body mass index and normalization of micronutrients in children with malnutrition - Keçeli Başaran, Meryem; Zengın, Nur; Doğan, Ali; Sursal, Alihan; Ozdener, Fatih (Journal of Surgery and Medicine, 2020)
Aim: Malnutrition is a serious and frequently encountered condition affecting more than 900 million individuals worldwide. Its relationship with negative clinical outcome, bad prognosis and susceptibility to diseases has been demonstrated in numerous studies alongside with the importance of early nutritional intervention. The aim of this study was to define the beneficial influence of a hypercaloric enteral supplement on body mass index (BMI) z-score as well as ferritin, vitamin B12 and vitamin D micronutrients. Methods: This study is a retrospective observational study. Records of patients who were diagnosed with malnutrition via a physician by having height and weight scores below -2 standard deviation were collected from Gaziosmanpaşa Training and Resource Hospital, Istanbul, Turkey. A comparative statistical analysis was performed on 205 pediatric malnutrition patients (ages 1 to 16) by gathering their BMI, ferritin, b12 and vitamin D at baseline with their measurements at 2 follow-up visits after the administration of hypercaloric (1.5kcal/mL) enteral supplement over 6 months. Results: There was a significant inverse correlation between BMI z-scores and the duration of enteral supplement administration, reflected by a 33.2% reduction of the mean BMI z-scores from -2.11 to -0.7 over 6 months (Z=-12.4, P<0.001). Additionally, there was a reduction in the number of patients with excessive or insufficient amounts of ferritin, b12 and vitamin D concentrations with 80%, 41.7% and 39.3% respectively over six months. Conclusions: Hypercaloric enteral supplementation is a short-acting and highly beneficial nutritional intervention in pediatric patients diagnosed with malnutrition, which provides a robust improvement in the BMI z-scores as well as a 2-tailed improvement of aforementioned micronutrients after six months of supplementation.